Anal Canal Duplication in an 11-Year-Old-Child. (15th September 2013) - Van Biervliet, S.; Maris, E.; Vande Velde, S.; Vande Putte, D.; Meerschaut, V.; Herregods, N.; De Bruyne, R.; Van Winckel, M.; Van Renterghem, K.
Abstract : Anal canal duplication (ACD) is the least frequent digestive duplication. Symptoms are often absent but tend to increase with age. Recognition is, however, important as almost half of the patients with ACD have concomitant malformations. We present the clinical history of an eleven-year-old girl with ACD followed by a review of symptoms, diagnosis, treatment, and prognosis based on all the reported cases in English literature.